AB0452 PREDICTIVE FACTORS FOR INSUFFICIENT RESPONSE TO INITIAL TREATMENT OR RECURRENCE IN PATIENTS WITH LUPUS ENTERITIS. (2nd June 2020) - Yoshida, Y.; Sugimoto, T.; Kohno, H.; Watanabe, H.; Mokuda, S.; Hirata, S.; Sugiyama, E.
Abstract : Background: Lupus enteritis (LE) is a rare but well-known complication of systemic lupus erythematosus (SLE). However, little knowledge about risk factors for insufficient response to initial treatment or recurrence have been reported. Objectives: To identify prognostic factors associated with poor response in patients with LE. Methods: Patients diagnosed as having LE at our hospital were consecutively registered from January 2009 to October 2019. The diagnosis of LE was made according to the criteria of BILAG 2004 which is defined as either vasculitis or inflammation of small or large bowel with supportive imaging and/or biopsy findings. Poor response was defined as insufficient response to initial therapy or relapse. We retrospectively compared clinical characteristics collected from medical records of the patients with good vs. poor response, using a non-parametric Wilcoxon signed-rank test for numerical variables and Fisher's exact test for categorical variables. Results: A total of 12 patients (16 episodes) diagnosed with LE were reviewed. The median age was 44.5 years and 11 were females. Six patients had a history of SLE (median disease duration; 3.0 years), of which 4 had a history of LE prior to the study period. And in the remaining 6 patients, LE was the primary symptom (Table 1 ). The comorbidities were 4 lupus cystitis, 1 biopsy-proven lupus nephritis, 1 pseudo-obstruction and 1 protein-losing enteropathy. Computed Tomography (CT) imaging of all 16 episodes showed small bowel wall thickening. Dilatation of intestine was observed in 81.3%, ascites in 81.3%, comb sign in 80.0% and target sign in 62.5%. When comparing clinical characteristics between the groups revealed that CT findings were similar in both groups, however serum CH50 levels (median (interquartile ranges (IQR)) 37.2 (25.3-46.9) U/mL vs 17.6 (7.1-21.4) U/mL, p=0.0095) were significantly lower in poor response group. Furthermore, patients who initiated glucocorticoids (GCs) at a lower dose (less than or equal to 0.6mg/kg prednisolone equivalent dose (PEQ)) was significantly more frequent in poor response group (Table 2 ). Conclusion: Lower level of CH50 and initial treatment with GCs at a lower dose were identified as prognostic factors associated with poor response to initial therapy or recurrence in LE. Disclosure of Interests: Yusuke Yoshida Grant/research support from: Astellas, Paid instructor for: Astellas, Tanabe Mitsubishi, Sanofi, Novartis, GlaxoSmithKline, Eli Lilly, Bristol-Myers Squibb, Chugai, Asahikasei, Eisai, Janssen, Speakers bureau: Astellas, Tanabe Mitsubishi, Sanofi, Novartis, GlaxoSmithKline, Eli Lilly, Bristol-Myers Squibb, Chugai, Asahikasei, Tomohiro Sugimoto: None declared, Hiroki Kohno: None declared, Hirofumi Watanabe: None declared, Sho Mokuda: None declared, Shintaro Hirata Grant/research support from: Eli Lilly, Consultant of: Bristol-Myers Squibb, UCB, Paid instructor for: AbbVie, Eisai, Tanabe-Mitsubishi, Speakers bureau: AbbVie, Eisai, Tanabe-Mitsubishi, Astellas, Ayumi, Bristol-Myers Squibb, UCB, Chugai, Eli Lilly, Janssen, Kissei, Sanofi, Takeda, Eiji Sugiyama Grant/research support from: AbbVie, Astellas, Ayumi, Kissei, Pfizer, Sanofi, Takeda, Tanabe-Mitsubishi, Bristol-Myers Squibb, Chugai, Eisai, Eli Lilly, Speakers bureau: AbbVie, Astellas, Ayumi, Kissei, Pfizer, Sanofi, Takeda, Tanabe-Mitsubishi, Bristol-Myers Squibb, Chugai, Eisai, Eli Lilly, Actelion